A Cognitive-Semantic Study of the Spatial Preposition Fi in the Quran (KEMANUSIAAN The Asian Journal of Humanities, 2017)
The existing literature has examined the preposition Fi ( ???) in the Quran from lexical syntactic perspective in strict spatio-geometric sense, but its abundant use with abstract concepts, emotions and states needs an elaborate approach to investigate its complex semantic functions. Therefore, this paper has taken a corpus based approach to investigate the functional semantic complexity of the preposition fi in the Quran from a cognitive perspective. The conceptual metaphor perspective holds that the sensorimotor neural structures define the use of spatial preposition in both spatio-geometric positions and abstract states. The linguistic data reveals that the container image schema is at work both in the literal and metaphoric use of spatial preposition fi. However, the preposition fi carries its own distinct semantic argument in each context and sometimes overrides the symmetry of container image schema. This paper recommends a broader perspective for a comprehensive analysis of spatial preposition fi and suggests further studies on its functional semantic complexity in the Quran.